Household sustainability: challenges and dilemmas in everyday life - Caeiro, Sandra (2021)
Recensão crítica da obra: "Household Sustainability: Challenges and Dilemmas in Everyday Life" de, Chris Gibson, Carol Farbotko, Nicholas Gill, Lesley Head, Lordon Waitt. Edward Elgar Publishing Limited, Cheltenham, UK and Massachusetts, USA (2013). 237 E-ISBN: 978-1-78100-621-4.